A Python-Based Interface Design for Electric Power System Education. - Yousef Marwan Alkhanafseh; Tahir Cetin Akinci (International Journal of Smart Grid and Sustainable Energy Technologies, 2021)
Python, which is widely used today, is one of the open-source programming languages. In the Python program, its interface is done through the PyQt5 library. With PyQt5, it is possible to develop object-based software that takes up less space on the disk and runs faster. In this study, an educational calculation and analysis program (ITUPSA) was designed for the Electric power systems course using the Python interface. Electric power systems are one of the fundamental courses in electrical engineering. This main course is taught in three sub-course groups as energy transmission-distribution, energy flow and energy economy. The energy transmission-distribution course package constitutes the first and most comprehensive part of the electric power systems group. In the energy transmission-distribution, the creation of the transmission line model and the calculation of the line parameters form an important part of the training. This section contains very detailed mathematical calculations and it is very important that students get the correct result as a result of these calculations. This can be possible with a lot of practice. The interface design was made by students and faculty to teach practical examples correctly. This developed (ITUPSA) python-based interface program is very suitable for calculation and analysis exercises in both undergraduate and graduate courses in the Electrical Engineering department. The purpose of this study is to create a python-based interface in order to solve the problems related to these lines, to make the types of short, medium and long power transmission lines correct and understandable. In the study, after selecting the type of energy transmission line and all parameters related to the line, the necessary mathematical analysis can be made and also the analysis results can be plotted. The analysis program is available in two languages, English and Turkish.